Photocatalytic Degradation of Rhodamine B Using CuS-doped ZnS Under Visible Light Irradiation - Rachel Mugumo; Shepherd M. Tichapondwa; Evans M. N. Chirwa (Chemical Engineering Transactions, 2022)
This study investigates the photocatalytic activity of CuS/ZnS in the degradation of Rhodamine B, an azo dye in textile wastewater generated through processing operations in textile industries which provides significant socioeconomic benefits. Nanoporous nanocomposites were synthesised via a one-pot thermal decomposition method which exhibited efficient photocatalytic activity. The microstructure and composition of the prepared catalyst was characterized using Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy-dispersive X-ray Spectroscopy (EDX) and X-Ray Diffraction (XRD). The degradation results showed that coupling pristine ZnS with the highly photosensitive CuS improved the photocatalytic degradation efficiency from 67 % to 88 % in 4 h under solar irradiation. This result clearly depicts the degradation efficacy improvement of ZnS when doped with CuS in rhodamine B degradation using visible light irradiation.